The Persistent Effect of Famine on Present-Day China: Evidence from the Billionaires - Pramod Kumar Sur; Masaru Sasaki (Institute of Labor Economics (IZA), 2021)
More than half a century has passed since the Great Chinese Famine (1959–1961), and China has transformed from a poor, underdeveloped country to the world's leading emerging economy. Does the effect of the famine persist today? To explore this question, we combine historical data on province-level famine exposure with contemporary data on individual wealth. To better understand if the relationship is causal, we simultaneously account for the well-known historical evidence on the selection effect arising for those who survive the famine and those born during this period, as well as the issue of endogeneity on the exposure of a province to the famine. We find robust evidence showing that famine exposure has had a considerable negative effect on the contemporary wealth of individuals born during this period. Together, the evidence suggests that the famine had an adverse effect on wealth, and it is even present among the wealthiest cohort of individuals in present-day China.
Keywords: D31; O15; N35; 330; famine; wealth; persistence; China